MR Lymphangiography: A Practical Guide to Perform It and a Brief Review of the Literature from a Technical Point of View - Mazzei, Francesco Giuseppe (Biomed Res Int, 2017)
We propose a practical approach for performing high-resolution MR lymphangiography (MRL). We shall discuss and illustrate the technical approach for the visualization of lymphatic vessels in patients suffering from lymphedema, how to distinguish lymphatic vessels from veins, and MRL role in supermicrosurgery treatment planning. A brief review of literature, from a technical point of view, is also reported.